Positional differences in absolute vs. relative training loads in elite academy soccer players - Douchet, T.; Paizis, C.; Babault, N. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The quantification of relative training loads (RTL) is useful to assess how much players are exposed to competitive demands during training [1,2]. However, this alternative method to absolute training loads (ATL) quantification has only been scarcely used. Most studies have mainly expressed the RTL without considering the position of the players. This study therefore aimed to evaluate ATL and RTL and compare positions over the full in-season in an elite soccer academy.